Morphological diversity of AlN nano- and microstructures: synthesis, growth orientations and theoretical modelling. (17th August 2020) - Nersisyan, Hayk H.; Lee, Jong Hyeon; Kim, Hyun You; Ryu, Seunhwa; Yoo, Bung Uk
ABSTRACT: Recent developments have seen breakthroughs in zero-, one-, two-, and three-dimensional AlN micro- and nanostructures, such as nanoparticles, nanowires, nanotubes, thin films and 3D multifold symmetry crystals. The attractive electrical, optical, and thermal properties of AlN make these materials irreplaceable for microelectrochemical systems (MEMS), surface acoustic waves (SAWs) and light emitting diodes (LED). The significant interest in the field of AlN nanostructure synthesis and application encouraged us to summarise the reported data to better understand the physical and chemical aspects of AlN crystal growth processes. Four main topics are covered in this review article: (1) the morphological diversity of AlN nano- and microstructures; (2) formation mechanisms and growth dynamics; (3) theoretical simulation of growth processes based on density functional theory (DFT) and phase field (PF) modelling approaches; (4) application and devices. This article also provides a perspective on future research relevant to AlN micro- and nanostructures.